Gangsters and G-men on screen : crime cinema then and now - Phillips, Gene D. (Lanham, Maryland : Rowman & Littlefield, 2014)
In this book, noted film and literature scholar Gene D. Phillips looks at the crime film genre. In addition to the usual suspects like Little Caesar, and The Godfather Part II, which he examines with a fresh perspective, Phillips also calls attention to some of the less heralded but no less worthy films and filmmakers that represent the genre.
CHAPTER TEN. BONNIE AND CLYDE AND THE UNTOUCHABLESCHAPTER ELEVEN. THE GRIFTERS AND THE DEPARTED; CHAPTER TWELVE. DILLINGER AND PUBLIC ENEMIES; AFTERWORD. GANGSTER SQUAD AND OTHER FILMS: Time Marches On and So Does the Gangster Genre; NOTES; BIBLIOGRAPHY; INDEX; ABOUT THE AUTHOR
Description based upon print version of record.
English
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gangster films -- History and criticism